Cardiovascular Effects Circular Training (Resistance-Interval) Combined with Berberine in Overweight Elderly Men - Ghorashi 1, Sayed Alireza; Zilaei Bouri 2*, Shirin; Azarbayjani 3, Mohammad ALi (Shahroud Journal of Medical Sciences, 2019)
Background: Obesity and overweight, along with inactive lifestyle, have been introduced as one of the most important for cardiovascular risk factors, especially in elderly. This study aimed to determine the effect of circular training (resistance-interval) combined with berberine on cardiovascular risk factors and C reactive protein (CRP) in overweight elderly men.Methods: Forty sedentary healthy elderly male aged 50-55 years divided into 4 groups: circular training (resistance-interval, 8 weeks, 3 times/weekly) (CT), berberine supplementation (BS), circular training combined with berberine (CT-BS) and control (CON) groups (n=10 each group). Intervention lasted 8 weeks. Fasting blood samples were collected before and 48 hours after lasted training session to determine cardiovascular risk factors (TG, TC, LDL, HDL) and serum CRP for all groups. Multivariate analysis of covariance (MANCOVA) used to compare groups results.Results: All interventions (CT, BS, CT-BS) resulted in significant decrease in TG, TC and LDL and increase in DL. Serum CRP was significantly decreased in CT and CT-BS groups but not in BS. In addition, significant difference was observed in cardiovascular risk factors and CRP within groups with emphasizing more cardiovascular effects of CT-BS.Conclusion: Based on the results, it is concluded that circular trainings combined with berberine supplementation is associated with more Cardiovascular effectiveness than each one alone in overweight elderly men.Keywords: Cardiovascular risk factor, Circular exercise, Berberine, Elderly, Overweight